Malingered Attention Deficit/Hyperactivity Disorder on the Conners' Adult ADHD Rating Scales: Do Reasons for Malingering Matter?. (September 2018) - Cook, Carolyn; Buelow, Melissa T.; Lee, Esther; Howell, Ashley; Morgan, Brittni; Patel, Kruti; Bryant, Andrew M.; Menatti, Andrew; Suhr, Julie
Malingering is a significant assessment concern in adults undergoing evaluations for attention deficit/hyperactivity disorder (ADHD) and may occur for a number of reasons, including access to medication and/or accommodations. Therefore, it is important to investigate ways to determine accuracy of self-reported ADHD symptoms. The present study used a simulation design to examine the impact of reasons for malingering on the Conners' Adult ADHD Rating Scales (CAARS) Symptom subscales and the CAARS infrequency index (CII). Participants ( N = 157) were randomly assigned to one of three conditions: best effort, malingering for stimulant medication, or malingering for extra time accommodations. The three groups were compared with 34 individuals reporting previous diagnosis of ADHD. Results showed that individuals in both malingering groups scored higher than controls on all CAARS subscales and CII. Individuals in the medication malingering group, but not the extra time malingering group, scored higher than the ADHD group on CII and several CAARS subscales whose content overtly reflects ADHD symptomatology. Findings emphasize the influence of malingering on self-reported ADHD symptoms and the need to assess for malingering in ADHD evaluation. Results also suggest that reason for malingering might differentially affect self-report of ADHD symptoms.